Biochemical studies on crossbreed cattle infected with Theileria in New Valley - Osman, Fathy Ahmad; H.I.M, Gaadee (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
Bovine tropical theileriosis is a fatal disease of sheep caused by the pathogenic species of protozoans of the genus Theileria. This study was designed to estimate the levels of plasma homocysteine (Hcy), serum thyroid hormones, the serum trace elements and to evaluate their correlations in different parasitemia rates in naturally Theileriosis in cattle. 39 crossbred cattle, about 1-3 years old, naturally infected with T. annulata were selected and divided into 3 subgroups according to parasitemia rates (<2%, 2-4%, 4-8%). 10 non-infected crossbred cattle were also selected as controls (clinical and laboratory healthy). Blood samples were collected and Hcy, thyroid hormones and major trace elements were measured.Significant decrease in the values of red blood cell count (RBC), packed cell volume (PCV) and hemoglobin confirmed that anemia had occurred in the infected cattle. Significant increase in Hcy, significant decrease in some trace elements (selenium and Zn), significant decrease in the values of thyroxine (T4) and (T4) but no remarkable changes in (FT3) and (FT4) were observed. Substantial elevations in plasma Hcy can potentially produce endothelial injuries and consequently help the formation of anemia. On the other hand, significant decrease in T4 and T3 and in some trace elements (selenium and Zn) besides the lack of any changes in the other related factors, indicate that the infection of cattle with different degree of parasitemia rates, can induce negative effects on the secretion and concentrations of thyroid hormones, some trace element but the infection could cause positive effects on important homocysteine.